1992
DOI: 10.1177/014860719201600120
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Tolerance and Nutritional Outcome Between a Peptide and a Standard Enteral Formula in Critically Ill, Hypoalbuminemic Patients

Abstract: Dipeptides have been reported to be more efficiently absorbed from the gastrointestinal tract than free amino acids. The objective of this study was to compare prospectively a peptide enteral formula (PEF) with a standard enteral formula (SEF) for tolerance and nutritional outcome in acutely injured, hypoalbuminemic (less than 3.0 g/dL) patients who require enteral nutrition support. The prevalence of diarrhea and elevated gastric residuals was assessed daily. Prealbumin, transferrin, colloid oncotic pressure,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(22 citation statements)
references
References 18 publications
1
21
0
Order By: Relevance
“…Some investigators have reported that peptide-based enteral diets are associated with better protein responses and less diarrhea compared to intact-protein diets[2,3]. On the other hand, others have reported that peptide-based formulas seem to offer no benefits over intact-protein diets in acutely injured, hypoalbuminemic patients[4]. However, while previous studies have described the small peptide formulas, no particular dipeptide- or tripeptide-based formulas have been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Some investigators have reported that peptide-based enteral diets are associated with better protein responses and less diarrhea compared to intact-protein diets[2,3]. On the other hand, others have reported that peptide-based formulas seem to offer no benefits over intact-protein diets in acutely injured, hypoalbuminemic patients[4]. However, while previous studies have described the small peptide formulas, no particular dipeptide- or tripeptide-based formulas have been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…In severely ill patients, the exocrine pancreatic function, which partially affects the digestion and absorption of certain nutrients, may be compromised (Mowatt-Larssen et al 1992). Under this condition, an oligomeric formula could prove advantageous over a complete protein formula.…”
Section: Applications To Critical or Intensive Carementioning
confidence: 99%
“…Patients with burns and traumatic injuries may experience GI motility problems [63,64]. In sepsis, exocrine pancreatic function is reduced, which can impair protein digestion [65]. Treatments for cancer and other conditions - for example, opiates, radiotherapy, or chemotherapy - have side effects of anorexia and impaired GI function [66].…”
Section: Choosing Which Enteral Formulation To Feedmentioning
confidence: 99%